2019
DOI: 10.4149/bll_2019_140
|View full text |Cite
|
Sign up to set email alerts
|

The effect of alpha‑lipoic acid on oxidative parameters and liver injury in rats with obstructive jaundice

Abstract: INTRODUCTION: The aim of this study is to investigate the effects of obstructive jaundice on the liver and effectivity of alpha-lipoic acid on liver damage and oxidative stress. MATERIALS AND METHODS: Thirty-six male Sprague-Dawley rats were divided into 3 groups per 12 animals, namely into Group I (control group): the bile duct was only mobilized by laparotomy, Group II (bile duct ligation group-BDL): the common bile duct was closed with clips and OJ was caused after laparotomy, and Group III (bile duct ligat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
(20 reference statements)
2
3
0
Order By: Relevance
“…Furthermore, we found that ALA significantly enhanced GPx, SOD, and CAT activity, whereas it inhibited MDA production under heat stress. This may partly explain the anti-oxidative action of ALA in vivo reported in previous studies [32,33]. Based on these results, we speculated that HS caused a decrease in anti-oxidative capacity and disrupted the balance between oxidative and antioxidative status.…”
Section: Discussionsupporting
confidence: 59%
“…Furthermore, we found that ALA significantly enhanced GPx, SOD, and CAT activity, whereas it inhibited MDA production under heat stress. This may partly explain the anti-oxidative action of ALA in vivo reported in previous studies [32,33]. Based on these results, we speculated that HS caused a decrease in anti-oxidative capacity and disrupted the balance between oxidative and antioxidative status.…”
Section: Discussionsupporting
confidence: 59%
“…Thus, in the present study, we analyzed the treatment outcomes of patients with surgical jaundice from the standpoint of the dynamic characteristics of the free radical processes involved. The relationship between free radical processes indicators and the severity of OJ was confirmed not only by our study but also by other studies conducted in different countries [ 21 , 22 , 34 , 35 , 36 , 42 , 43 , 44 , 45 , 46 , 47 ]. In animal models and in patients with OC, a marked increase in plasma levels of oxidative stress markers was recorded, while the level of antiperoxidase activity paradoxically decreased.…”
Section: Discussionsupporting
confidence: 90%
“…The analysis of the samples obtained proved that FRP indices differ significantly between healthy individuals and patients with obstructive jaundice. Therefore, it is not surprising that, based on the earlier studies, other researchers are trying to find drugs to normalize free radical processes in patients with jaundice [ 31 , 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%